2014
DOI: 10.1016/j.neuroimage.2014.08.044
|View full text |Cite
|
Sign up to set email alerts
|

Resting state connectivity immediately following learning correlates with subsequent sleep-dependent enhancement of motor task performance

Abstract: There is ongoing debate concerning the functions of resting-state brain activity. Prior work demonstrates that memory encoding enhances subsequent resting-state functional connectivity within task-relevant networks and that these changes predict better recognition. Here, we used functional connectivity MRI (fcMRI) to examine whether task-induced changes in resting-state connectivity correlate with performance improvement after sleep. In two separate sessions, resting-state scans were acquired before and after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 42 publications
6
56
0
Order By: Relevance
“…Finally, although we did not evidence a decrease of the boost effect in old as compared with young adults in the MEG procedure, we might expect an age‐related decrease in the ability to consolidate new motor skills as previously reported [Brown et al, ; Fogel et al, ; Spencer et al, ; Wilson et al, ]. Moreover, resting state might prepare new motor skills for later consolidation during sleep, as rsFC post‐learning changes were related to sleep‐dependent memory improvement in young adults [Gregory et al, ]. However, sleep‐dependent memory consolidation was not investigated in the present study.…”
Section: Discussionsupporting
confidence: 47%
“…Finally, although we did not evidence a decrease of the boost effect in old as compared with young adults in the MEG procedure, we might expect an age‐related decrease in the ability to consolidate new motor skills as previously reported [Brown et al, ; Fogel et al, ; Spencer et al, ; Wilson et al, ]. Moreover, resting state might prepare new motor skills for later consolidation during sleep, as rsFC post‐learning changes were related to sleep‐dependent memory improvement in young adults [Gregory et al, ]. However, sleep‐dependent memory consolidation was not investigated in the present study.…”
Section: Discussionsupporting
confidence: 47%
“…In healthy individuals, significant performance improvements occur after sleep but not after wake (49, 93-95) and correlate with N2 duration (49) and spindle density (50, 96, 97). In contrast, chronic medicated SZ patients fail to show significant sleep-dependent improvement despite normal learning during training (31, 73, 98-100) and this failure correlated with sleep spindle density in one study (31), but not in two others (73, 100).…”
Section: Reduced Spindles Are Associated With Impaired Cognition and mentioning
confidence: 99%
“…We previously reported that increased resting-state connectivity in the motor network, measured immediately after learning a finger tapping motor sequence task (MST) (Karni et al, 1998), predicts sleep-dependent performance improvement measured the following day (Gregory et al, 2014). Using the same data set, we now demonstrate that self-reports of the amount of time spent spontaneously thinking about the task during this post-training rest correlates with connectivity between a different set of brain regionsthose that were activated during task training.…”
Section: Introductionmentioning
confidence: 62%
“…No such correlations were found between task-related thought and connectivity in task-related regions during the pretask scan, suggesting that the correlations with thinking about the task do not reflect trait-like patterns of functional connectivity. We have previously shown that connectivity of these regions did not correlate with learning of the task, as measured by either MST performance improvement during training or subsequent sleep-dependent improvement (Gregory et al, 2014). Post-training thought also did not correlate with task-related activation seen during MST training, either in any of the significant regions identified in the primary analysis (Fig.…”
Section: Resting-state Connectivity Related To Thoughtmentioning
confidence: 80%
See 1 more Smart Citation